A ternary Ag/TiO2/CNT photoanode for efficient photoelectrochemical water splitting under visible light irradiation. (23rd March 2017) - Chaudhary, Deepti; Singh, Simrjit; Vankar, V.D.; Khare, Neeraj
Abstract: A ternary Ag/TiO2 /CNT photoanode was prepared by grafting Ag nanoparticles on the surface of as-synthesized TiO2 /CNT nanocomposite for the photoelectrochemical (PEC) water splitting under visible light irradiance. The ternary composite photoanode was observed to generate four times higher photocurrent density compared to binary TiO2 /CNT nanocomposite under visible light irradiance. The Ag nanoparticles on the surface of nanocomposite act as a surface plasmon resonance (SPR) photosensitizer under visible light. The enhanced photocurrent density of Ag/TiO2 /CNT ternary photoanode is attributed to the increased light absorption in the visible region, decrease in band-bending and effective interfacial electron transfer due to the synergetic effect of Ag nanoparticles and CNTs. The enhanced charge transfer within the Ag/TiO2 /CNT was also confirmed by the electrochemical impedance spectroscopy. This work demonstrates a feasible route to improve the PEC performance of TiO2 towards water splitting under sunlight irradiation. Highlights: Ag/TiO2 /CNT nanocomposite was synthesized by grafting Ag nanoparticles on TiO2 /CNT. Ag/TiO2 /CNT exhibits enhanced photoelectrochemical water splitting performance. Ag nanoparticles act as a surface plasmon resonance (SPR) photosensitizer. Ag/TiO2 /CNT shows four times higher current density than the binary one.